The intercultural sensitivity levels of primary health care workers in a city in Eastern Turkey - Sema Cifci; Vasfiye Bayram Deger (Journal of the Pakistan Medical Association, 2021)
Objective: This descriptive study aimed to examine the intercultural sensitivity levels and related factors of primary healthcare workers who provide health services to the people of Mardin, a city which hosts a variety of socioethnic groups. Methods: The study population consisted of all of the primary care health workers (n=150) in Mardin, a city located in the southeast of Turkey that receives a lot of immigrants from Syria. A total of 131 health workers were included in the study. Results: The total mean score of the intercultural sensitivity scale of the participants was found to be 73.30 ±16.7. The findings showed that the most important factor in the level of intercultural sensitivity was “Interaction Engagement”. It was revealed that there was a strong relationship between the subscales of “Responsibility and Interaction Attentiveness” and “Respect for Cultural Differences” (r= .703, p<.01). Considering the intercultural sensitivity levels of the participants and several variables, a statistically significant difference was found between the job titles of the participants, their status of friendship in different countries, the opportunity to be with people in other cultures for any reason, the status of willingness to work in different cultures and their intercultural sensitivity scale scores (p<0.05). Conclusions: The results of the study showed that the level of cultural sensitivity of the healthcare professionals working in primary care was moderate while it was relatively low among doctors, nurses/midwives and other medical staff. Keywords: Culture, Intercultural Sensitivity, Healthcare Workers, Turkey, Mardin Continuous...